PENGEMBANGAN LATIHAN SOAL MEMBACA PEMAHAMAN BAHASA JERMAN MELALUI MEDIA ZEP QUIZ - Feriansyah, Zidny Hudan; Titaley, Audrey Gabriella (LATERNE, 2025)
Reading comprehension is one of the essential skills in learning a foreign language, including German. However, students often feel bored with conventional reading exercises. This research addresses two main problems: how the development process of German reading comprehension exercises using ZEP Quiz is conducted, and how feasible the developed exercises are after validation. The objective of this study is to describe the steps in developing reading comprehension exercises using ZEP Quiz and to evaluate their feasibility based on expert assessments. The method used is Research and Development (R&D) following the Borg & Gall model, which consists of five stages: research and information gathering, planning, developing the initial product, limited trial, and initial product revision. The data were obtained through questionnaires completed by content experts and media experts to assess the validity and quality of the developed product. The validation result from the content expert was 95%, indicating that the exercises are highly suitable for use. Meanwhile, the media validation result was 96%, showing that ZEP Quiz is highly feasible as a learning medium.